Progression of experimental lesions of atherosclerosis: Assessment by kinetic modeling of black‐blood dynamic contrast‐enhanced MRI. Issue 6 (24th July 2012) - Chen, Huijun; Ricks, Jerry; Rosenfeld, Michael; Kerwin, William S.
Abstract: Pharmacokinetic modeling of dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) is used to noninvasively characterize neovasculature and inflammation in atherosclerotic vessels by estimating perfusion characteristics, such as fractional plasma volume v p and transfer constant K trans . DCE‐MRI has potential to study the evolution of nascent lesions involving early pathological changes. However, currently used bright‐blood DCE‐MRI approaches are difficult to apply to small lesions because of the difficulty in separating the signal in the thin vessel wall from the adjacent lumen. By suppressing the lumen signal, black‐blood DCE‐MRI techniques potentially provide a better tool for early atherosclerotic lesion assessment. However, whether black‐blood DCE‐MRI can detect temporal changes in physiological kinetic parameters has not been investigated for atherosclerosis. This study of balloon‐injured New Zealand White rabbits used a reference‐region‐based pharmacokinetic model of black‐blood DCE‐MRI to evaluate temporal changes in early experimental atherosclerotic lesions of the abdominal aorta. Six rabbits were imaged at 3 and 6 months after injury. K trans was found to increase from 0.10 ± 0.03 min −1 to 0.14 ± 0.05 min −1 ( P = 0.01). In histological analysis of all twelve rabbits, K trans showed a significant correlation with macrophage content ( R = 0.70, P =0.01). These results suggest black‐blood DCE‐MRI and a reference‐region kinetic model could be used to study plaque development and therapeutic response in vivo. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.